PEMBELAJARAN AKSELERASI (Konsep Belajar Cepat Abad – XX1) - Mutia (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2020)
The accelerated program is an educational service program according to the potential intelligence and special talents of students, by providing the opportunity to complete the program in a shorter time. The purpose of this research is to examine how the acceleration program is implemented, the learning curriculum, learning objectives, and the acceleration implementation model. The accelerated learning program focuses on the education of gifted children with 8 (eight) types of intelligence, namely language linguistic intelligence, mathematical logic, visual spatial, bodily kinesthetic, musical, interpersonal, intrapersonal, and natural. This program helps educators carry out the learning process according to the intelligence possessed by each individual. Abstrak Program akselerasi adalah program pelayanan pendidikan sesuai potensi kecerdasan dan bakat istimewa yang dimiliki siswa, dengan memberi kesempatan untuk dapat menyelesaikan program dalam waktu yang lebih singkat. Tujuan penelitian ini adalah mengkaji bagaimana implementasi program akselerasi, kurikulum pembelajaran, sasaran pembelajaran, dan model pelaksanaan akselerasi. Program pembelajaran akselerasi menitik beratkan kepada pendidikan anak berbakat dengan 8 (delapan) jenis kecerdasan yaitu kecerdasan linguistik bahasa, logika matematika, visual spasial, kinestetik tubuh, musical, interpersonal, intrapersonal, dan natural. Program ini membantu para pendidik dalam melaksanakan proses pembelajaran sesuai dengan kecerdasan yang dimiliki setiap individu.